Flesh and Fire: Embodiment and Sacrality in the Myth of Draupadi (Erothanatos: A Peer-Reviewed Quarterly Journal on Literature, 2025)
This paper examines Chitra Banerjee Divakaruni’s The Palace of Illusions through the interconnected frameworks of embodiment, sacrality, and ritual control, with particular attention to feminist retellings of myth. While Draupadi has long been depicted in the Mahābhārata as both divine and disruptive—born of fire yet condemned for catalysing war—her voice has traditionally been silenced within patriarchal narrative structures. Divakaruni’s retelling shifts this dynamic by granting Draupadi first-person narration, thereby transforming her from an object of epic discourse into a subject of her own story. The analysis situates Draupadi’s experiences within the context of Ritual theory, Victor Turner’s liminality, Catherine Bell’s concept of ritualisation as power, feminist critique, Luce Irigaray's notion of the “Other”, Julia Kristeva’s theory of abjection and semiotic disruption, and embodiment studies, which highlight how myths inscribe meaning onto female bodies. Episodes such as her miraculous birth, polyandrous marriage, and humiliation in the dice hall are read as ritual spectacles that both sacralise and subjugate her body, yet also provide grounds for resistance. By foregrounding Draupadi’s emotions—shame, rage, desire—as counter-rituals, Divakaruni reimagines fire not as destiny but as inner strength. The study argues that The Palace of Illusions functions as a feminist intervention, reclaiming Draupadi’s voice, challenging patriarchal ritual control, and demonstrating the transformative potential of mythological retellings.
Keywords: Embodiment, Sacrality, Ritual Control